DIGITAL TRANSFORMATION OF THE FINANCIAL SECTOR IN INDIA: EVOLUTION, ISSUES AND CHALLENGES (International Journal of Food and Nutritional Sciences, 2022)
India's financial sector has undergone significant digital transformation, driven by advances in technology, supportive government policies, and a growing demand for real-time, user-friendly financial services. This paper explores the evolution of digital finance in India, identifies key issues and challenges and proposes recommendations to address them. The study aims to provide insights into how digital innovation is reshaping the financial ecosystem and the steps needed to make it more inclusive, secure and sustainable.